Are we overestimating internal rotation gait by conventional modelling? - Musagara, Arik Rehani; Salami, Firooz; Oelmaier, Hannah; Götze, Marco; Wolf, Sebastian Immanuel (Gait & posture, 2023)
Background - The determination of the knee joint axis (KJA) via specific calibration movements has become a promising alternative to the conventional approach to determine this axis based on regression equations or directly via marker placement on bony landmarks of the knee. Since the orientation of the KJA may differ between methods, it has direct influence on hip rotation and may therefore influence clinical decision making in context of transverse plane gait deviations. Research question: Does a functional KJA calibration lead to clinically relevant differences in hip rotation estimates during gait compared to the conventional method? - Methods - 95 subjects (age: 19.9 years; BMI: 21.1 kg/m2), including 71 patients with potential rotation malalignment, were prospectively examined and underwent 3D gait analysis. For the conventional approach the KJA was determined by applying a knee alignment device, for the functional approach subjects were asked to perform two different calibration movements. Each procedure was performed twice. Mean hip rotation in stance (mHipRotSt) was determined following the conventional and the functional KJA calibration. - Results - Deming regression analysis for the comparison of conventional and functionally measured hip rotation revealed a systematic and substantial difference between methods (slope: 0.63; intercept: 0.31°). Measurement repetition with the knee alignment device revealed typical errors around 5°, whereas the functional methods lead to profoundly smaller errors around 1-2° with slightly inferior results for SQUAT compared to FLEX. However, when compared to conventional frontal plane video-taping, the conventional method seemed to reflect the more consistent results. - Significance - The systematic linear discrepancy in mHipRotSt obtained by a functional approach as compared to the conventional approach appears critical since patients with severe internal or external rotation gait may be misjudged in function when receiving corrective procedures such as femoral derotation osteotomy.
Online verfügbar 25. April 2023, Artikelversion 26. April 2023
Gesehen am 16.06.2023